The Effect Of Facilities And Motivation On Work Productivity At The Prof. Dr. Moestopo University Dental Hospital (B) - Anggia Nurul Hizana; Budiharto Budiharto; Rahayu Rahayu (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2026)
This study aims to analyze the simultaneous effect of Facilities and Motivation on Work Productivity at Prof. Dr. Moestopo (B) Dental and Oral Hospital. This research employs quantitative methods with a cross-sectional approach. The sample was selected using a simple random sampling technique. Data collection was conducted through questionnaires distributed to 82 dental clinical clerkship students. The data were analyzed using validity tests, reliability tests, descriptive analysis, and inferential statistics. The results show that Facilities have a positive and significant effect on the dental clinical clerkship students' work productivity. Similarly, Motivation has a positive and significant effect on the dental clinical clerkship students' work productivity. Together, Facilities and Motivation simultaneously affect the dental clinical clerkship students' work productivity at Prof. Dr. Moestopo (B) Dental and Oral Hospital